Water handling challenge on hydrolysis of sodium borohydride in batch reactors - M. J. F. Ferreira (2012)
A study was undertaken in order to investigate the potential of hydrogen (H 2) generation by hydrolysis of solid sodium borohydride (NaBH 4) with stoichiometric amount of distilled water (from molar ratios H 2O/NaBH 4 (mol/mol) of 2 to 18), in the presence of a powder nickel-ruthenium based catalyst, reused more than 300 times. The experiments, performed in batch reactors with different free volumes and bottom shapes (flat and conical) reveal - for the conical bottom shape with any excess of water - 8.1 H 2 wt% and 92 kg H 2/m 3 (materials-only basis), and a H 2 rate of 87.4 L(H 2) min -1 g -1 catalyst, at the moderate pressure of ∼1.2 MPa. The results presented in this work give emphasis to the importance of considering the role of reactor bottom geometry on the solid NaBH 4 hydrolysis studies performed with stoichiometric amounts of liquid water. Copyright (c) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights.